2017
DOI: 10.1249/mss.0000000000001087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Motivational Self-Talk on Endurance and Cognitive Performance in the Heat

Abstract: Motivational self-talk is effective in altering the internal psychophysiological control of exercise and plays a role in improving endurance capacity and executive function in the heat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 36 publications
1
42
1
6
Order By: Relevance
“…Motivational self-talk (Barwood, Corbett, Wagstaff, McVeigh, & Thelwell, 2015;Blanchfield et al, 2014) and psychological skills training packages (Barwood, Thelwell, & Tipton, 2008) appear to reduce perception of effort, and they have been shown to improve endurance performance. Another study, however, found that using motivational self-talk when performing in the heat did not reduce perception of effort and, instead, helped performers to perform for a longer duration when they reached near-maximal levels of effort (Wallace et al, 2017). In addition, mental fatigue (Van Cutsem et al, 2017) and emotion suppression (Wagstaff, 2014) increase perception of effort and detrimentally affect endurance performance.…”
Section: Psychobiological Modelmentioning
confidence: 97%
See 2 more Smart Citations
“…Motivational self-talk (Barwood, Corbett, Wagstaff, McVeigh, & Thelwell, 2015;Blanchfield et al, 2014) and psychological skills training packages (Barwood, Thelwell, & Tipton, 2008) appear to reduce perception of effort, and they have been shown to improve endurance performance. Another study, however, found that using motivational self-talk when performing in the heat did not reduce perception of effort and, instead, helped performers to perform for a longer duration when they reached near-maximal levels of effort (Wallace et al, 2017). In addition, mental fatigue (Van Cutsem et al, 2017) and emotion suppression (Wagstaff, 2014) increase perception of effort and detrimentally affect endurance performance.…”
Section: Psychobiological Modelmentioning
confidence: 97%
“…laboratory and field research could also examine whether certain strategies are efficacious at helping athletes to cope with stressors that are simulated under controlled conditions (for examples of the effects of interventions for coping with performing in the heat, see Barwood et al, 2008;Wallace et al, 2017).…”
Section: Self-regulation In Endurance Sports 25mentioning
confidence: 99%
See 1 more Smart Citation
“…A high variance in the efficacy of psychological skills training has been demonstrated relative to several interrelated agendas appropriate to exercise performance optimisation, including tolerance to environmental extremes and pain [70,105,106].…”
Section: Applicationsmentioning
confidence: 99%
“…Gaoua, Grantham, Racinais, and El Massioui (2012) showed an increase in NA in very hot environments (50˚C) and suggested that the subjective state of the individual might be the main factor affecting cognitive performance in hot environments. Physical activity under thermal stress is also associated with NA (Kobrick & Johnson, 1991;Lane, Terry, Stevens, Barney, & Dinsdale, 2004;Wallace et al, 2017). According to Beedie, Terry, and Lane (2000), it is advisable to evaluate affect during stressful exercise because it can predict performance and reflect the individual's ability to cope with an opponent (Acevedo & Ekkekakis, 2001).…”
Section: Introductionmentioning
confidence: 99%